Electronic phase transition in CrN thin films grown by reactive RF magnetron sputtering. Issue 12 (15th June 2022) - Alam, Khan; Haider, Mohammad B.; Al-Kuhaili, Mohammad F.; Ziq, Khalil A.; Haq, Bakhtiar Ul
Abstract: Chromium nitride thin films were prepared by reactive radio frequency magnetron sputtering on glass and Si(001) substrates. Thin films were grown at different nitrogen to argon flow rate ratio and their effect on the film composition, band gap and electronic phase transition was studied by different experimental technique. X-ray diffraction analyses establish that CrN films predominantly grow in [111] CrN and [002] CrN directions irrespective of the substrates used for the growths. The band gap was found to vary with the composition of the films. All films are semiconducting at room temperature and show discontinuity in their resistivity versus temperature curve indicating electronic transition. But the low temperature electronic phase depends on the growth conditions and composition of the films.